The Future of Information Technology Development in Schools under the Bangkok Metropolitan Administration in the Next Decade - Chongpeeradechanon , Suvullapa; Phaivitayasiritham, Chaiyos (Journal of Education Studies, Chulalongkorn University, 2020)
The purpose of this research is to study the futures Scenario of information technology development of schools in Bangkok in the next decade.This study uses the EDFR (Ethnographic Delphi Futures Research) methodology and includes expert interviews with 21 people; data was anlayzed by percent, mean, and median. Interquartile Range were practiced in the data analysis. Then was also a focus group comprising 6 experts. The results of the research are as follows: 1) The curriculum should be developed according to the current and modern context via online learning. 2) The hardware / software should be allocated with efficiency and sufficient numbers such as computer and high-speed internet service.Software type and learning media should be online system that allow students to study and review the lessons by themselves. 3) Effectiveness and quality assurance should be achieved using an online system in order to manage, inspect, and evaluate all aspects according to the national education standards. 4) The style of teaching and learning should support teachers to produce any online media and students should be able to access the content by using their own communication equipment. 5)Organization management should have the center of educational information services that offer current and accurate information including the teachers’ training in relating knowledge and technology use.